An endoscopic transnasal prelacrimal recess transmaxillary approach to the pterygopalatine fossa and infratemporal fossa - Liu, Jian; Yang, Zhijun; Lu, Bin; Bi, Zhiyong; Liu, Pinan (Frontiers in Surgery, 2023)
Objective: In this paper the author's goal was to present the anatomic nuances and their clinical experience with lesions of the pterygopalatine fossa and infratemporal fossa using endoscopic transnasal prelacirmal recess transmaxillary approach (PLRMA).Methods: An endoscopic anatomical dissection of three fresh cadaveric heads was performed bilaterally to evaluate the feasibility of the PLRMA. Prior to dissection, stereotactic computed tomography (CT) scans were obtained for each head to obtain anatomical measurements. The area of exposure on the posterior wall of maxillary sinus was determined using stereotaxis. Six patients with schwannomas or epidermoid cysts who underwent the transnasal prelacirmal recess transmaxillary approach were illustrated.The mean area of exposure on the posterior wall of maxillary was 9.55cm 2 . Total resection was achieved in all six patients. The mean follow-up time was 16 months, one patient complained of postoperative facial numbness, which gradually improved. No cases of chronic sinusitis were reported.The endoscopic transnasal prelacrimal recess transmaxillary approach provides efficient operative exposure to the pterygopalatine fossa and infratemporal fossa. Preserving the integrity of the mucosa on the nasal lateral wall is an advantage of this approach.